2020
DOI: 10.3390/brainsci10110822
|View full text |Cite
|
Sign up to set email alerts
|

Combining Magnetization Transfer Ratio MRI and Quantitative Measures of Walking Improves the Identification of Fallers in MS

Abstract: Multiple sclerosis (MS) impacts balance and walking function, resulting in accidental falls. History of falls and clinical assessment are commonly used for fall prediction, yet these measures have limited predictive validity. Falls are multifactorial; consideration of disease-specific pathology may be critical for improving fall prediction in MS. The objective of this study was to examine the predictive value of clinical measures (i.e., walking, strength, sensation) and corticospinal tract (CST) MRI measures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…33 Surveys show that mobility impairment is a top symptom of importance to people with MS. [16][17][18][19] Greater walking impairment, and more severe overall impairment, is experienced in the progressive compared with the relapsing remitting phase, with indications of greater impairments in primary compared with secondary progressive MS. 33 As mobility impairment increases, functional limitations can lead to safety concerns with increased likelihood of falls, and greater barriers to participation in rehabilitation. 34 Mobility studies investigating the biological mechanisms of impairment and recovery at molecular, cellular, and synaptic levels are encouraging; some focus exclusively on progressive MS. 35 These provide preliminary evidence of the potential impact of exercise on neuroprotection and regeneration in animal models 36 and humans. 10,37 While these mechanistic studies vary in methodological quality, these inter-disciplinary collaborations provide a foundation for future work to inform the design of rehabilitation interventions.…”
Section: Mobility and Upper Extremity Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Surveys show that mobility impairment is a top symptom of importance to people with MS. [16][17][18][19] Greater walking impairment, and more severe overall impairment, is experienced in the progressive compared with the relapsing remitting phase, with indications of greater impairments in primary compared with secondary progressive MS. 33 As mobility impairment increases, functional limitations can lead to safety concerns with increased likelihood of falls, and greater barriers to participation in rehabilitation. 34 Mobility studies investigating the biological mechanisms of impairment and recovery at molecular, cellular, and synaptic levels are encouraging; some focus exclusively on progressive MS. 35 These provide preliminary evidence of the potential impact of exercise on neuroprotection and regeneration in animal models 36 and humans. 10,37 While these mechanistic studies vary in methodological quality, these inter-disciplinary collaborations provide a foundation for future work to inform the design of rehabilitation interventions.…”
Section: Mobility and Upper Extremity Impairmentmentioning
confidence: 99%
“…33 Surveys show that mobility impairment is a top symptom of importance to people with MS. 16–19 Greater walking impairment, and more severe overall impairment, is experienced in the progressive compared with the relapsing remitting phase, with indications of greater impairments in primary compared with secondary progressive MS. 33 As mobility impairment increases, functional limitations can lead to safety concerns with increased likelihood of falls, and greater barriers to participation in rehabilitation. 34…”
Section: Mobility and Upper Extremity Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our lab has demonstrated associations between neuroimaging metrics and fall risk [9], including the utility of combining clinical measures with quantitative imaging metrics to improve identi cation of fallers in PwMS [10][11]. Given the complexity and diversity of factors associated with fall risk, it is likely that several brain regions are contributing to fall risk as well.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, DTI studies have shown lower fractional anisotropy in the corticospinal tract (CST), superior cerebellar peduncles (SCP), and corpus callosum (CC) relating to worse walking performance in PwMS 6–8 . Similarly, MTR studies have demonstrated correlations between lower MTR values and worse motor function 6,9 in PwMS. Yet, DTI and MTR imaging exhibit limited specificity to the interpretation of results 10 .…”
Section: Introductionmentioning
confidence: 99%